IMPLEMENTASI MODEL OBSERVASI DAN SIMULASI (OBSIM) UNTUK MENINGKATKAN KEMAMPUAN MENGAJAR AWAL MAHASISWA PENDIDIKAN GURU FISIKA SEKOLAH MENENGAH - Indrawati, - (2010)
A study on "Implementation of Observation and Simulation Model (Obsim Model) for Improving the Initial Teaching Ability of High School Physics Teacher Education Students" was carried out for three purposes. Firstly, this studi investigates how Obsim Model can improve the student initial teaching ability. Secondly, it finds out whether Obsim Model can improve the student initial teaching ability and lastly this study proves whether Obsim Model is more better than the traditional one for improving the student initial teaching ability. This study involved two activities namely 'main model test' and 'comparative model test'. The main model test used action research with 'the one group pretest post-test design' to investigate Obsim Model in improving the students' initial teaching ability, while the comparative model test applied 'the matching only pretest-posttest control group design' to investigate whether Obsim Model is more better than the traditional one. The subject for the main test was 20 physics education students taking the subject of Teaching and Learning Strategy; the students were third semester students, year 2002/2003, who were studying in a State University in East Java. On the other hands, the subject for comparative study involved 38 students, third semester students, year 2003/2004 who were studying in the same university. The subject of comparative test (n=38) was divided into two groups, 19 students as the experimental group, while the rest as the control one. Both of those two groups have approximately the same cummulative grade average during the first and the second semesters (IPK rata-rata = 2,6). The final data of comparative test were 35 students (18 sudents of the experimental group and 17 students of the control group). The findings reveal that Obsim Model is able to improve initial teaching ability for the high school physics teacher education students as long as teaching simulations which are given by the lecturer are presented clearly, students participate actively in class discussion, the task of making a lesson plan is often done by students, and student clarity teaching skills always are given feedback. Moreover, the study shows that Obsim Model is better than the traditional one for improving the student initial teaching ability.